(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2018)
This paper re-examines psychoanalytic formulations of disappointment. Using the philosophical insights of Karl Jaspers, I propose that existential analysis could more usefully focus on the phenomenon of Enttäuschung (disillusionment), the client’s confrontation with the reality of situations and the adoption of their attitude towards this.